A resistência dos Jerivás: criar refúgio com a permacultura, em uma paisagem rural em Agudo-RS - Vieira, Luiza de Albuquerque Leite (2024)
The urgency of the climate and socio-environmental crisis of our time, often referred to as the Anthropocene, confronts us for the first time with the threat to global habitability. The unprecedented pace of these changes challenges our political responsiveness. In this scenario, “refugia” emerge as places of interest, enabling the renewal of cultural and biological diversity after significant disturbances. This research aimed to comprehend the complex dynamics related to the creation of habitability in a rural landscape in Agudo-RS, at the Jerivá Permaculture Station. The study sought to understand how care practices, permeated by permaculture ethics, and the interdependence between humans and non-humans in this landscape influence the formation of refuge. Through situated ethnography, it was possible to develop a narrative that highlights multispecies encounters and possible alliances among differences, creating patches of multispecies habitability in a landscape ruined by the simplifying and predatory economic logics of the plantation. The potential theoretical and practical contributions of this research point towards the necessity for deceleration and practices of attention, both regarding the processes of scientific research and the everyday practices that shape the world we live on.